PENGEMBANGAN MEDIA PEMBELAJARAN PRAKTIKUM KIMIA MENGGUNAKAN CAMTASIA STUDIO 8 DI SMA NEGERI 1 SIPIROK TAHUN AJARAN 2016 - 2017 - Viva Mulyana; Abubakar Abubakar; Sahlan Tuah (Universitas Muhammadiyah Tapanuli Selatan, 2017)
This study to design, construct and test the feasibility of the learning media useCamtasia Studio 8 and to get information whether by developing learning media of chemistry practicum using Camtasia Studio 8 more effectively and efficiently. The results of the research are: (1) The process of making media using Camtasia Studio 8 includes identification of competence, scriptwriting, media design, animation making, audio making, program testing techniques, expert review, repair, final product. Based on the assessment of media experts, the learning media using Camtasia Studio 8 deserves to be used as a learning video media. (2) The data of the lecturers' lecture in terms of the feasibility aspects of the contents of the first lecturer with a score of 33 and the second lecturer get a score of 27. The language eligibility of the first lecturer score of 31 and the second lecturer get a score of 27. Feasibility of presentation of the first lecturer with a score of 13 and lecturers both received a score of 11. (3) Assessment of the first subject teachers if viewed from the aspect of eligibility of the content with the score obtained 31 as well as from the second subject teachers. The language eligibility of the first subject teacher scores 30, while the second subject teacher scores 27. The eligibility of the presentation of the first and second subject teachers also earns the same score of 13. Overall, the average overall score of this learning video medium is 4.13. Keywords:Development of Chemical Practical Learning Media, Camtasia Studio 8, Solubility and Solubility Times.